Pain in the genital: a clue to a rare injury - Er, Lay Ze; Johar MJ, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
In trauma, a systematic approach has been developed to assist physician and surgeon in identifying immediate life-threatening injuries so that prompt intervention can save lives and reduce mortality. This approach also called for a head-to-toe examination so that other injuries are not missed out. Sacral fracture, although rare, but could have serious complications. The present case discusses about a trauma patient who presented with complain of genitalia pain with normal genitalia examination. Sacral fracture was not suspected and was only detected when a pelvic radiograph was ordered as part of the trauma survey. Fortunately, the patient had no complications resulting from the injury itself. The aim of the presentcase is to discuss the importance of investigating beyond patient’s complaint, as in this case the patient only complained of genitalia pain which ended up as a sacral fracture.